2017
DOI: 10.20473/jn.v6i1.3971
|View full text |Cite
|
Sign up to set email alerts
|

Terapi Kelompok Terapeutik Anak dengan Orang Tua dan Guru Meningkatkan Perkembangan Mental Anak Usia Sekolah

Abstract: Introduction: School aged called as intelectual time in industrial development stage. Industrial development stage is important in human development stages. The purpose of this tudy was to know the effect of school aged therapeutic group therapy to mental development.Methods: The design was quasi experimental pre-post test with control group. One hundred and sixteen children at 9–11 years old were used as sample of this study that divided to 38 children on first intervention group (childparents), 36 children o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Empowering mental health cadres through TGT training for school children (little cadres) indicates a rise in areas of job development, higher self-esteem, and a decrease in symptoms of prodroma early psychosis in school children (Noviyanti et al, 2019). Istiana et al (2011) showed that the results of providing TGT contributed to increasing knowledge, psychomotor and creative development of school children.…”
Section: Discussionmentioning
confidence: 99%
“…Empowering mental health cadres through TGT training for school children (little cadres) indicates a rise in areas of job development, higher self-esteem, and a decrease in symptoms of prodroma early psychosis in school children (Noviyanti et al, 2019). Istiana et al (2011) showed that the results of providing TGT contributed to increasing knowledge, psychomotor and creative development of school children.…”
Section: Discussionmentioning
confidence: 99%